Visualizing the replicating HSV-1 virus using STED super-resolution microscopy - Li, Zhuoran (Virol J, 2016)
BACKGROUND: Replication of viral genome is the central event during the lytic infectious cycle of herpes simplex virus 1 (HSV-1). However, the details of HSV-1 replication process are still elusive due to the limitations of current molecular and conventional fluorescent microscopy methods. Stimulated emission depletion (STED) microscopy is one of the recently available super-resolution techniques allowing observation at sub-diffraction resolution. METHODS: To gain new insight into HSV-1 replication, we used a combination of stimulated emission depletion microscopy, fluorescence in situ hybridization (FISH) and immunofluorescence (IF) to observe the HSV-1 replication process. RESULTS: Using two colored probes labeling the same region of HSV-1 genome, the two probes highly correlated in both pre-replication and replicating genomes. In comparison, when probes from different regions were used, the average distance between the two probes increased after the virus enters replication, suggesting that the HSV-1 genome undergoes dynamic structure changes from a compact to a relaxed formation and occupies larger space as it enters replication. Using FISH and IF, viral single strand binding protein ICP8 was seen closely positioned with HSV-1 genome. In contrast, ICP8 and host RNA polymerase II were less related. This result suggests that ICP8 marked regions of DNA replication are spatially separated from regions of active transcription, represented by the elongating form of RNA polymerase II within the viral replication compartments. Comparing HSV-1 genomes at early stage of replication with that in later stage, we also noted overall increases among different values. These results suggest stimulated emission depletion microscopy is capable of investigating events during HSV-1 replication. CONCLUSION: 1) Replicating HSV-1 genome could be observed by super-resolution microscopy; 2) Viral genome expands spatially during replication; 3) Viral replication and transcription are partitioned into different sub-structures within the replication compartments.